India, habermas and the normative structure of public sphere - Ali, Muzaffar (London : Routledge, 2023)
"The book examines how the contemporary Indian situation poses a strict theoretical challenge to Habermas's theorization of the public sphere and employs the method of samvāda to critically analyze and dissect its universalist claims. It invites the reader to consider the possibility of imagining a normative Indian public sphere that is embedded in the Indian context-in a native and not nativist sense-to get past the derivative language of philosophical and political discourses prevalent within Indian academia. The book proposes that the dynamic cooperative space between Indian political theory and contemporary Indian philosophy is effectively suited to theorize the native idea of the Indian public sphere. It underlines the normative need for a natively theorized Indian public sphere to further the multilayered democratization of public spheres within diverse communities that constitute Indian society. The book will be a key read for contemporary studies in philosophy, political theory, sociology, postcolonial theory, history, and media and communication studies"
Keywords: Sociology; Indian Nationalism